2018
DOI: 10.1002/prep.201700286
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐dependent Elastic Coefficients of β‐HMX from Molecular Simulations

Abstract: The second-order elastic stiffness tensor and isotropic moduli of b-octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (b-HMX, P2 1 /n space group setting) on the 0 K isotherm are presented for hydrostatic pressures between 10 À4 GPa and 30 GPa. The results were obtained from molecular statics simulations using a validated all-atom flexible-molecule force field. Comparisons to previous experimental and computational determinations are provided.Keywords: linear elasticity · constitutive model · equation of state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…These deviations are partly derived from the absence of anharmonic softening with temperature. Previous molecular dynamics studies have shown the SOECs of β ‐HMX at 300 K are in accordance well with experiments, reflecting that such temperature softening effects are significant to determine the SOECs of energetic materials accurately. Furthermore, the bulk modulus ( B = 12.80 GPa) and shear modulus ( G = 7.45 GPa) are calculated within Voigt–Reuss–Hill approximations .…”
Section: Resultssupporting
confidence: 79%
“…These deviations are partly derived from the absence of anharmonic softening with temperature. Previous molecular dynamics studies have shown the SOECs of β ‐HMX at 300 K are in accordance well with experiments, reflecting that such temperature softening effects are significant to determine the SOECs of energetic materials accurately. Furthermore, the bulk modulus ( B = 12.80 GPa) and shear modulus ( G = 7.45 GPa) are calculated within Voigt–Reuss–Hill approximations .…”
Section: Resultssupporting
confidence: 79%
“…The MD simulations were performed using LAMMPS Plimpton (1995) in conjunction with a modified version of the all-atom, fully flexible, non-reactive force field originally developed for HMX by Smith and Bharadwaj (S-B). Smith and Bharadwaj (1999); Bedrov et al (2000); Kroonblawd et al (2016); Mathew and Sewell (2018); Chitsazi et al (2020) Intramolecular interactions in the S-B force field are modeled using harmonic functions for covalent bonds, three-center angles, and improper dihedral ("wag") angles; and truncated cosine expansions for proper dihedrals. Intermolecular non-bonded interactions between atoms separated by three or more covalent bonds (i.e., 1-4 and more distant intramolecular atom pairs) are modeled using Buckingham-plus-charge (exponential-6-1) pair terms.…”
Section: Force Fieldmentioning
confidence: 99%
“…The stiffness matrix of β-HMX has a moderate anisotropy that changes with pressure. Experimental measurements obtained by stimulated thermal pulse scattering [36] and molecular dynamics simulations [37] were used to complement and study their pressure dependence [18,38]. A thirdorder polynomial interpolation provides the elastic coefficients for a pressure of 800 MPa (Table 1).…”
Section: Numerical and Theoretical Frameworkmentioning
confidence: 99%
“…β-HMX elastic coefficients at 298 K and 0 MPa from [36]. Data (in GPa) at 800 MPa have been extracted from [14,38]. (0.00,0.00,1.0 meshing software, GMSH [44], is used to generate a 200 μm side mesh cube.…”
Section: Numerical and Theoretical Frameworkmentioning
confidence: 99%